Price Competitiveness and Service Quality Have an Impact on Ship Agency Contributions - Maemunah, Siti; Damanik, Ade Irfani Nugraha; Yuliyanto, Agus; Sembiring, Honny Fiva Akira; Sugiyanto, Sugiyanto; Setiawan, Edhie Budi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The study aims to determine the relationship between price, service quality, customers’ satisfaction, and competitiveness on ship agency services and their impact on PT. Maritel Bahtera Abadi Marunda as mediated by the ship agency services. A sample of 100 respondents from PT. Maritel Bahtera Abadi Marunda, consists of company’s competitors and consumers of the Ship Agency Sector, was taken from the primary data using Quantitative method with Explanatory research design. The correlation coefficient analysis method, path analysis tests, and hypothesis testing were used to test instrument and classical assumption testing. The findings show a relationship between price, service quality, customers’ satisfaction, and competitiveness between ship agency services in PT. Maritel Bahtera Abadi Marunda. The practical implications provide direction for adopting the impact of price and service quality in increasing the competitiveness of ship agency services and consumers’ behavior.